Use of Remdesivir in Mild to Moderate COVID -19 Disease and its Clinical Outcomes: A Single-Center Observational Study - Beenish Syed; Elisha Shalim; Ishfaque Memon; Anika Farhan (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To assess the usefulness of Remdesivir in mild-moderate COVID-19 and its effects on clinical outcomes and mortality. Methodology: This was observational study conducted at Sindh Infectious Diseases Hospital. July 2020 to March 2022. Demographic and clinical data were collected retrospectively from the patient’s medical records. Patients > 18 years of age and admitted with confirmed SARS-COV 2 of the mild-moderate category were included. For analysis, patients were divided into two groups to compare those who received Remdesivir plus Standard of Care (SOC) and those receiving only Standard of Care. Outcome variables included progression to severe disease, duration of hospital stay, respiratory support, and mortality. Results: A total of 789 patients were admitted, of which 435 (54.5%) had mild and 363 (45.5%) had moderate COVID-19 infection. Out of these, 46.13% received Remdesivir, while 55% of patients received SOC. The median age of patients in the Remdesivir group was 62 (IQR 50-72) years (p<0.05). No significant difference in mortality was observed between the two groups. (4.4 vs. 3.2%, P>0.05). Patients in the SOC group exhibited a significant risk of disease progression [61(14%) vs23(6.3%), odds ratio (OR):2.425 95% CI: 1.45-4.06, p<0.05]. A significantly longer hospital stay in the SOC group was seen in both mild and moderate disease categories (p<0.05). Conclusion: Remdesivir can be effective in patients with mild to moderate COVID-19 to halt the progression to severe disease and shorten the hospital stay, leading to early recovery and reduced risk of complications. Keywords: Mild-moderate COVID-19, Remdesivir, low-flow oxygen, decreased severity, reduced mortality